2006
DOI: 10.1007/s00244-005-1057-9
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Three Antifouling Agents on Algal Communities and Algal Reproduction: Mixture Toxicity Studies with TBT, Irgarol, and Sea-Nine

Abstract: The toxicity of three antifoulants (Sea-Nine, Irgarol, and TBT) was determined individually and in mixtures in two tests with microalgae. Effects on periphyton community photosynthesis and reproduction of the unicellular green algae Scenedesmus vacuolatus were investigated. The tested antifoulants were highly toxic in both tests. Observed mixture toxicities were compared with predictions derived from two concepts: Independent Action (IA), assumed to be more relevant for the tested mixtures that were composed o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 55 publications
(31 citation statements)
references
References 52 publications
3
27
1
Order By: Relevance
“…Moreover, results clearly showed that the combination of TBT and UVBR stresses has synergistic effects affecting the first trophic levels of the marine food web [28]. Finally, the inhibition of photosynthesis of periphyton community has been observed after exposure to TBT (EC 50 = 0.02 mg L −1 ) [3].…”
Section: Antifouling Biocidesmentioning
confidence: 90%
See 4 more Smart Citations
“…Moreover, results clearly showed that the combination of TBT and UVBR stresses has synergistic effects affecting the first trophic levels of the marine food web [28]. Finally, the inhibition of photosynthesis of periphyton community has been observed after exposure to TBT (EC 50 = 0.02 mg L −1 ) [3].…”
Section: Antifouling Biocidesmentioning
confidence: 90%
“…These facts make them ideal candidates for testing mixture models based on the chemical mode of action and understanding the physiological mechanisms behind possible interactions [85,90]. Mixture toxicity studies focused on single species [85,86], natural communities in laboratory experiments [3,82,91], or outdoor microcosms and mesocosms [83,[92][93][94] data. Many reviews and critical analysis have shown that synergistic interactions within pesticide mixtures and realistic low-dose chemical mixtures in species are a rather rare phenomenon, constituting very low percentages of the tested mixture combinations and often occurs at high concentrations [87,[95][96][97][98][99][100][101].…”
Section: Tlili Et Al (2011) [89]mentioning
confidence: 99%
See 3 more Smart Citations